Antibacterial activity and mechanism of luteolin isolated from Lophatherum gracile Brongn. against multidrug-resistant Escherichia coli - Ding, Yahao; Wen, Guilan; Wei, Xingke; Zhou, Hao; Li, Chunjie; Luo, Zhengqin; Ou, Deyuan; Yang, Jian; Song, Xuqin (Frontiers in Pharmacology, 2024)
Infections caused by multidrug-resistant (MDR) bacteria have become a major challenge for global healthcare systems. The search for antibacterial compounds from plants has received increasing attention in the fight against MDR bacteria. As a medicinal and edible plant, Lophatherum gracile Brongn. (L. gracile) has favorable antibacterial effect. However, the main antibacterial active compound and its antimicrobial mechanism are not clear. Here, our study first identified the key active compound from L. gracile as luteolin. Meanwhile, the antibacterial effect of luteolin was detected by using the broth microdilution method and time-kill curve analysis. Luteolin can also cause morphological structure degeneration and content leakage, cell wall/membrane damage, ATP synthesis reduction, and down-regulation of mRNA expression levels of sulfonamide and quinolones resistance genes in multidrug-resistant Escherichia coli (MDR E. coli). Furthermore, untargeted UPLC/Q-TOF-MS-based metabolomics analysis of the bacterial metabolites revealed that luteolin significantly changed riboflavin energy metabolism, bacterial chemotaxis cell process and glycerophospholipid metabolism of MDR E. coli. This study suggests that luteolin could be a potential new food additive or preservative for controlling MDR E. coli infection and spread.